Fiscal policy, government size and EMU business cycle synchronization. (1st November 2019) - Bunyan, Sabrina; Duffy, David; Filis, George; Tingbani, Ishmael
Abstract: We provide new evidence on the effects of fiscal policy and government size on pairwise business cycle synchronization in EMU. A novel time‐varying framework is employed to estimate business cycle synchronization and subsequently a panel approach is used to establish the role of fiscal variables in determining the pairwise synchronization observations across time. The findings suggest similarities in the size of the public sector, yet divergence in fiscal policy stance, matter for the determination of business cycle synchronization. Hence, increased fiscal federalism in EMU will contribute to increased business cycle synchronization. Our results remain robust to different specifications and sub‐periods.